2021
DOI: 10.2196/30690
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness and Cost-effectiveness of Videoconference-Based Integrated Cognitive Behavioral Therapy for Chronic Pain: Randomized Controlled Trial

Abstract: Background Cognitive behavioral therapy is known to improve the management of chronic pain. However, the components of this therapy are still being investigated and debated. Objective This study aimed to examine the effectiveness of an integrated cognitive behavioral therapy program with new components (attention-shift, memory work, video feedback, and image training) delivered via videoconferencing. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
“…The following observations only occurred once in the literature: decrease in anger [26], decrease in decision conflict [30], decrease in decision regret [30], decreased digestive disturbance [26], decreased pain [26], increased medication adherence [41], and the intervention had no effect on self-efficacy [34]. [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56] 19 Reduced anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 3 more Smart Citations